Arbitraging Covered Interest rate Parity Deviations and Bank Lending - Keller, Lorena (American Economic Review, 2024)
I propose and test a new channel through which covered interest rate parity (CIP) deviations can affect bank lending in emerging economies. I argue that when CIP deviations exist, banks attempt to arbitrage them. To do so, banks must borrow in a particular currency. When this currency is scarce, bank lending in the currency required to arbitrage decreases, while they use this currency in their arbitrage activities. I test this channel by exploiting differences in the abilities of Peruvian banks to arbitrage CIP deviations. I find evidence that supports the proposed channel. (JEL F31, G01, G13, G21, O16)